Total Knee Arthroplasty Is Superior to Open Wedge High Tibial Osteotomy in Terms of Pain Relief for Patients With Osteoarthritis - Kosuke Hamahashi, MD, PhD; Genya Mitani, MD, PhD; Tomonori Takagaki, MD; Kenji Serigano, MD, PhD; Yoshiki Tani, MD, PhD; Masato Sato, MD, PhD; Masahiko Watanabe, MD, PhD (Arthroplasty Today, 2021)
Background: Globally, total knee arthroplasty (TKA) is widely performed on patients with osteoarthritis. Meanwhile, open wedge high tibial osteotomy (OWHTO) has garnered attention in our country as a joint-preserving procedure. This study aimed to retrospectively compare the postoperative clinical outcomes of TKA and OWHTO for patients with osteoarthritis. Methods: We selected 94 patients (106 knees) who underwent OWHTO or TKA between 2013 and 2018, had complete clinical data, and were followed up for >2 years. Patients were classified into 2 groups depending on the procedure (TKA: n = 49; OWHTO: n = 45). Patients in the A (= arthroplasty) group were significantly older, with a worse range of motion (ROM) than those in the O (osteotomy) group. There were no significant differences regarding sex and body mass index between groups. Operative time, perioperative blood loss, knee ROM, and Japanese Knee Injury and Osteoarthritis Outcome Score (J-KOOS) were compared between the groups. Results: Significant differences were found between the A and O groups regarding operative time (120 ± 27.2 vs 80.3 ± 23.3 minutes), perioperative blood loss (505.4 ± 271.8 vs 322.6 ± 196.1 mL), knee ROM (flexion; 123.4 ± 16.3° vs 133.7 ± 12.8°), and J-KOOS for pain (87.4 ± 12.5 vs 78.1 ± 15.2 points) and symptoms (86.6 ± 12.3 vs 79.1 ± 13.3 points). There were no significant differences regarding other J-KOOS subscales. Conclusions: OWHTO involved shorter operative times and less blood loss. However, the O group reported less pain relief. The A group represents an older, likely less active patient population. Therefore, OWHTO is a possible joint-preserving treatment options in younger active patients who may not be interested in arthroplasty.